Evaluation of biochemical and protein biomarkers analysis in type 2 diabetes mellitus - Kamal Uddin Zaidi; Firoz Naem Khan; Vijay Thawani; Richa Parmar (Wolters Kluwer Medknow Publications, 2019)
Introduction: Diabetes mellitus (DM) type 2 (T2) is a metabolic disorder characterized by insulin resistance and affecting protein metabolism. There has been a great interest in the proteomic analysis of plasma and serum for the identification and characterization of protein biomarkers of different diseases. Materials and Methods: For the protein identification, one of the most important developments and technologies is the proteomics. In this work, the levels of protein biomarkers specific to T2 DM using sodium dodecyl sulfate polyacrylamide gel electrophoresis were identified and characterized. Results: Patients suffering from DM and normal healthy controls were recruited for this study. Biochemical and proteins biomarker assay were done. Some proteins were up and down-regulated in the samples of diabetes as compared to control. Conclusion: Assessment of the levels of biomarkers can aid early diagnosis and as well cure of T2DM.